Prevalence of Rape Incidences in Rigasa Neighbourhood in Kaduna State, Nigeria - Saminu , Idris; Modibbo, Samira Isah (Kashere Journal of Politics and International Relations, 2023)
Insecure locations in northern Nigeria appear to have a high rate of sexual violence against children and young adults. Many incidents have been reported and prosecuted, but the number of incidents in the region continues to rise regularly. The prevalence of multiple instances is significantly higher in slum-like settings, densely populated places with a high degree of overcrowding. The cause of this surge in sexual violence in minors is still being debated. The paper aims to examine the prevalence of rape cases in the Rigasa area of Kaduna state. Hence, this paper assesses the daily increase in rape cases in the Rigasa neighborhood. Predicated on Routine Activity Theory (RAT), the paper utilized secondary data sources and qualitatively analyzed the prevalence of rape cases in the Rigasa area of Kaduna state. The findings of the paper revealed that high population density, absence of protectors, and availability of suitable victims and potential perpetrators contributed to the high prevalence of rape cases in the area. The paper recommends that the Kaduna State Government and Non-Governmental Organizations should liaise with the community to provide orientation on the laws of the state and on how best to guard their children and women against the perpetrators of rape.